Fabrication and characterisation of Cr and Co doped Bi1.5Zn0.92Nb1.5O6.92 pyrochlores - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
Cr and Co doped Bi1.5Zn0.92Nb1.5O6.92 pyrochlore ceramics were produced by solid state mixing of oxides. Cr and Co were doped into the Nb and Nb-Zn sites considering the compositions of Bi1.5Zn0.92Nb1.5-xCrxO6.92-x, (Bi1.5Zn0.46)(Zn0.46-3x/6Nb1.5-3x/5Crx)O6.92-x2 for Cr doping and Bi1.5Zn0.92Nb1.5-3x/5CoxO6.92, (Bi1.5Zn0.46)(Zn0.46-3x/6Nb1.5-3x/5COx)O6.92-x/2 for Co doping. The solubility limit of Cr in BZN was higher than that of Co and the solubility limit increased when doping was made both into Nb and Zn sites. The second phases appeared when x > 0.2 for Cr and x > 0.15 for Co doping into the Nb-Zn sites. Simultaneous Cr doping into the Nb- and Zn-sites of BZN pyrochlore gave higher dielectric constant than doping into the Nb-site of pyrochlore. However, Co doping into the Nb- and Zn-sites and only into the Nb-site of BZN gave identical dielectric results in the range of 202-218. The temperature coefficient of dielectric constant decreased with Cr doping and increased with Co doping. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Powders-solid state reaction; Sintering; Dielectric properties; Bismuth zinc niobate pyrochlore; DIELECTRIC-PROPERTIES; CRYSTAL-CHEMISTRY; CERAMICS